Neuroplasticity Mechanisms in Frontal Brain Gliomas: A Preliminary Study - Mitolo, Micaela; Zoli, Matteo; Testa, Claudia; Morandi, Luca; Rochat, Magali Jane; Zaccagna, Fulvio; Martinoni, Matteo; Santoro, Francesca; Asioli, Sofia; Badaloni, Filippo; Conti, Alfredo; Sturiale, Carmelo; et al. (Frontiers in Neurology, 2022)
Background: Pathological brain processes may induce adaptive cortical reorganization, however, the mechanisms underlying neuroplasticity that occurs in the presence of lesions in eloquent areas are not fully explained. The aim of this study was to evaluate functional compensatory cortical activations in patients with frontal brain gliomas during a phonemic fluency task and to explore correlations with cognitive performance, white matter tracts microstructural alterations and tumor histopathological and molecular characterization. Methods: Fifteen patients with frontal glioma were preoperatively investigated with an MRI study on 3T scanner and a subgroup underwent an extensive neuropsychological assessment. The hemispheric laterality index(LI) was calculated through phonemic fluency task fMRI activations in the frontal, parietal, and temporal lobe parcellations. Diffusion-weighted images were acquired for all patients and for a group of 24 matched healthy volunteers. Arcuate Fasciculus(AF) and Frontal Aslant Tract(FAT) tractography was performed using constrained spherical deconvolution diffusivity modeling and probabilistic fiber tracking. All patients were operated with a resective aim, then underwent adjuvant therapies, depending on the final diagnosis. Results: All patients during phonemic fluency task fMRI showed left hemispheric dominance in temporal and parietal regions. Regarding frontal regions (i.e. frontal operculum) we found right hemispheric dominance that increases when considering only those patients with tumor located on the left side. These latter activations positively correlate with verbal and visuo-spatial short-term memory, and executive functions. No correlations were found between left frontal operculum and cognitive performance. Furthermore, patients with IDH-1 mutation and without TERT mutation, showed higher rightward frontal operculum fMRI activations and better cognitive performance in tests measuring general cognitive abilities, semantic fluency, verbal short-term memory and executive functions. As for white matter tracts, we found left and right AF and FAT microstructural alterations in patients with, respectively, left-sided and right-side glioma compared to controls. Conclusions: Compensatory cortical activation of the corresponding region in the non-dominant hemisphere and its association with better cognitive performance and more favorable histopathological and molecular tumor characteristics shed light on the neuroplasticity mechanisms that occur in the presence of a tumor, helping to predict the rate of post-operative deficit, with the final goal of improving patients’quality of life.